Correlation between lower uterine wall thickness measured by transabdominal ultrasonography and cervical length measured by transvaginal ultrasonography in Thai pregnant women. Issue 1 (January 2019) - Woraboot, Wanitchar; Wanitpongpan, Prapat; Phaophan, Amprapha
Abstract : Background: Preterm labor is one of major obstetric challenges and can be predicted by cervical length at mid-trimester. In some settings, transvaginal ultrasound is not available and the screening and prevention of preterm labor will be suboptimal. We hope to find a correlation between other marker i.e. lower uterine wall thickness measured by transabdominal ultrasonography and cervical length measured by transvaginal ultrasonography in Thai pregnant women during 16–32 weeks of gestation. Methods: This study was a cross-sectional study. 166 singleton pregnant women were invited to participate in the study between June 2015 and December 2015. Transabdominal ultrasonography was performed to measure the lower uterine wall thickness and transvaginal ultrasonography was performed to measure the cervical length. The Spearman's rank correlation was used to evaluate the correlation between the two parameters. The inter-observer variation was assessed by using Bland–Altman plot. The outcomes of all pregnancies were followed and only those who delivered at term were included for the calculation of normal value of lower uterine wall thickness. Results: There was a highly positive correlation between lower uterine wall thickness and cervical length (rs = 0.767, n = 166, p < 0.001). For those who had short cervical length (defined as less than 30 mm) at GA 16–24 weeks (n = 10), the mean corresponding lower uterine wall thickness was 4.4 mm (SD 0.50). The inter-observer variation of the measurement of lower uterine wall thickness and cervical length were small. The lower uterine wall thickness tended to be slightly thinner when the gestation advanced. (mean 5.4 mm at 16–20 weeks and 5.1 mm at 28–32 weeks). Conclusion: There was a highly positive correlation between lower uterine wall thickness measured by transabdominal ultrasonography and cervical length measured by transvaginal ultrasonography in Thai pregnant women.